2009
DOI: 10.1182/blood-2008-09-179762
|View full text |Cite
|
Sign up to set email alerts
|

A proliferation-inducing ligand mediates follicular lymphoma B-cell proliferation and cyclin D1 expression through phosphatidylinositol 3-kinase–regulated mammalian target of rapamycin activation

Abstract: A proliferation-inducing ligand (APRIL), as well as its receptors transmembrane activator and calcium-modulating cyclophilin ligand (CAML) interactor (TACI) and B-cell maturation antigen (BCMA), has been shown to be important in B-cell biology, and overexpression of APRIL in mice results in development of lymphoma. Limited data are available on APRIL-specific signaling responses, but knockout models suggest that signaling through TACI is critical to B-cell homeostasis. To better understand the mechanism by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 66 publications
3
36
0
Order By: Relevance
“…Similar staining was observed in all 10 specimens. These observations, in concert with similar results recently reported in diffuse large cell lymphoma, 26 follicular lymphoma, 33 T-cell ALL 34 and Philadelphia chromosome-positive ALL, 18 provide a potential rationale for targeting both complexes simultaneously.…”
Section: Results Mtorc1 and Mtorc2 Substrates Are Phosphorylated In Csupporting
confidence: 88%
“…Similar staining was observed in all 10 specimens. These observations, in concert with similar results recently reported in diffuse large cell lymphoma, 26 follicular lymphoma, 33 T-cell ALL 34 and Philadelphia chromosome-positive ALL, 18 provide a potential rationale for targeting both complexes simultaneously.…”
Section: Results Mtorc1 and Mtorc2 Substrates Are Phosphorylated In Csupporting
confidence: 88%
“…14 At the same time, Hodgkin and Reed-Sternberg (HRS) cells express many genes of activated B cells, indicating that the oncogenic program of cHL may arise in the process of deregulation of mechanisms, controlling activity of NF-B, 15 ERK, 16 and JAK/STAT 17 pathways in activated B cells. In addition, AKT and ERK kinases are frequently constitutively activated in different B-lymphoma entities, including follicular lymphoma (FL), 18 diffuse large BCL (DLBCL), 19 Burkitt lymphoma (BL), 20 and cHL. 21,22 Therefore, it has been hypothesized that FOXO1 inactivation might be a common event contributing to lymphomagenesis in several lymphoma entities.…”
Section: Introductionmentioning
confidence: 99%
“…Available data indicates tumor-promoting activity of APRIL, not only in various B-cell malignancies but also in human cancer of colon, thyroid or breast [26][27][28][29]. Moreaux et al demonstrated that APRIL activated NF-kB, PI-3kinase/AKT, and MAPK kinase pathways in myeloma cells and induced a strong up-regulation of the antiapoptotic proteins Mcl-1 and Bcl-2 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreaux et al demonstrated that APRIL activated NF-kB, PI-3kinase/AKT, and MAPK kinase pathways in myeloma cells and induced a strong up-regulation of the antiapoptotic proteins Mcl-1 and Bcl-2 [28]. Gupta et al reported that APRIL mediates follicular lymphoma B-cell proliferation [29]. Furthermore, APRIL, through binding heparin sulfate proteoglycans (HSPG) on the surface of tumor cells, may ini- www.fhc.viamedica.pl tiate a solid tumor growth through the regulation of tumor cells adhesion and invasion [16,17].…”
Section: Discussionmentioning
confidence: 99%